Seismicity and Crustal Structure of the Southern Main Ethiopian Rift: New Evidence From Lake Abaya. (28th July 2021) - Ogden, C. S.; Keir, D.; Bastow, I. D.; Ayele, A.; Marcou, S.; Ugo, F.; Woodward, A.; Kibret, B. A.; Gudbrandsson, S.
Abstract: The Main Ethiopian Rift (MER) has developed during the 18 Ma‐Recent separation of the Nubian and Somalian plates. Extension in its central and northern sectors is associated with seismic activity and active magma intrusion, primarily within the rift, where shallow ( < 5 km) seismicity along magmatic centers is commonly caused by fluid flow through open fractures in hydrothermal systems. However, the extent to which similar magmatic rifting persists into the southern MER is unknown. Using data from a temporary network of five seismograph stations, we analyze patterns of seismicity and crustal structure in the Abaya region of the southern MER. Magnitudes range from 0.9 to 4.0; earthquake depths are 0–30 km. V P / V S ratios of ∼ 1.69, estimated from Wadati diagram analysis, corroborate bulk‐crustal V P / V S ratios determined via teleseismic P‐to‐S receiver function H ‐ κ stacking and reveal a relative lack of mafic intrusion compared to the MER rift sectors to the north. There is a clear association of seismicity with the western border fault system of the MER everywhere in our study area, but earthquake depths are shallow near Duguna volcano, implying a shallowed geothermal gradient associated with rift valley silicic magmatism. This part of the MER is thus interpreted best as a young magmatic system that locally impacts the geothermal gradient but that has not yet significantly modified continental crustal composition via rift‐axial magmatic rifting. Plain Language Summary: The East African Rift in Ethiopia captures the transition from continental rifting in the south to incipient seafloor spreading in the north. A consensus has emerged over the past two decades that a significant proportion of extension in the Ethiopian rift is accommodated by magma intrusion, not faulting and plate stretching. However, in the southernmost, least mature, part of the rift, sub‐surface geophysical constraints are lacking, meaning where/how magmatic extension occurs is unknown. Using a new network of seismograph stations in the Lake Abaya region of the southern Main Ethiopian Rift, we constrain crustal thickness and the first earthquake catalog for the southern Main Ethiopian Rift. Earthquakes are mostly located along the western margin of the rift and persist to lower crustal depths. Only near the Duguna volcano are earthquakes confined to the upper crust, implying magmatic modification of the crust due to magmatic extension is not yet established in this rift sector. Key Points: New seismograph network constraints seismicity and crustal structure in the southern Main Ethiopian Rift (MER) Clear association of seismicity with the western border fault system, not in‐rift faults associated with the magmatic extension Wadati diagram analysis and low receiver function‐derived bulk crustal V P / V S ratios reveal the southern MER is a magma‐poor rift sector